Dielectric Properties of Natural Ester Mixed with Nanoparticles under Thermal Stress - Kittikhuntharadol, Yannaphol; Vittayakorn, Wanwilai; Pattanadech, Norasage (My University, 2020)
This paper aim to study of the dielectric properties of thermal stressed natural ester mixed with TiO2, and ZnO. Polarization and depolarization current (PDC) along with dielectric loss factor (tanδ) of the test specimens were investigated. The test specimens comprised of unmodified natural ester and natural ester mixed with different volume concentration, i.e., 0.01%, and 0.03% of TiO2, and ZnO. After preparing the natural ester and the natural ester nanofluid specimen, such specimens were undergone with thermal stress at 110 degree Celsius for 72 hours in vacuum oven. Then, a PDC-Analyser-1MOD was utilized for PDC measurement of the test samples. For tanδ measurement, test circuit was set-up according to IEC 60247 and the C and tanδ meter with the liquid electrode were used. From the test result, thermal stress strongly affects the PDC and tanδ characteristics of the liquid samples. Besides, natural ester mixed with 0.01% of TiO2 concentration shows the high potential dielectric liquids compared with other specimens.
Keywords: nanofluids; nanoparticles; natural ester; PDC; stressed; tan δ